Plasma acetylcholine and nicotinic acid are correlated with focused preference for photographed females in depressed males: an economic game study - Hiroaki Kubo; Daiki Setoyama; Motoki Watabe; Masahiro Ohgidani; Kohei Hayakawa; Nobuki Kuwano; Mina Sato-Kasai; Ryoko Katsuki; Shigenobu Kanba; Dongchon Kang; Takahiro A. Kato (Scientific Reports, 2021)
Abstract Interpersonal difficulties are often observed in major depressive disorder (MDD), while the underlying psychological and biological mechanisms have not yet been elucidated. In the present case–control study, a PC-based trust game was conducted for 38 drug-free MDD patients and 38 healthy controls (HC). In the trust game, participants invested money in a partner (trusting behaviors), and also rated each partner’s attractiveness (preference for others). In addition, blood biomarkers including metabolites were measured. Both MDD and HC males exhibited more trusting behaviors compared to females. MDD males’ preference for ordinary-attractive partners (lay-person photographs) was lower than HC males, whereas their preference for high-attractive females (fashion-model photographs) was similar levels to HC males. This tendency in MDD males could reflect a “focused (narrowed) preference for females”. As for blood biomarker analysis, the levels of 37 metabolites including acetylcholine, AMP, GMP, nicotinic acid and tryptophan were significantly different between two groups. Interestingly, among male participants, acetylcholine and nicotinic acid were negatively correlated with the level of focused preference for photographed females. In sum, we have revealed some behavioral, psychological and biological traits of trusting behaviors and preference for others especially in MDD males. Larger studies should be conducted to validate our preliminary findings.